Advertising and sales promotion - Kaser, Ken (South-Western Cengage Learning, 2013)
includes bibliographical refernces and index; This book is a comprehensive introduction to the principles and practices of advertising. The course explores the social, ethical, and legal issues of advertising, historical influences, strategies, and media decision processes as well as integrated marketing communications